Impact of Self-Regulated Learning and Academic Intelligence on Student Behaviour and Cognitive Development (International Journal of Scientific Research in Science and Technology, 2025)
The study investigates the interconnected roles of metacognitive strategies and intellectual capacities in shaping student outcomes. In contemporary educational contexts, learning is no longer perceived as a passive reception of knowledge but as an active, self-directed process where students take ownership of their academic journey. Self-regulated learning, defined as the ability to plan, monitor, and evaluate one’s own learning activities, fosters autonomy, persistence, and adaptability, enabling students to overcome challenges through strategic effort. Academic intelligence, encompassing cognitive abilities such as reasoning, memory, comprehension, and problem-solving, provides the foundational capacities that support learning. The integration of these constructs demonstrates that intelligence alone does not guarantee academic success; rather, it is the effective regulation of intellectual resources through self-monitoring and self-discipline that leads to meaningful educational achievement. This study highlights that the impact of self-regulated learning and academic intelligence extends beyond academic performance into the domain of behaviour and personality development. Students who demonstrate strong self-regulatory capacities tend to cultivate constructive behavioural patterns such as responsibility, resilience, and collaborative engagement, while also avoiding maladaptive tendencies like procrastination and academic disengagement. Similarly, the cognitive development associated with academic intelligence—enhanced critical thinking, metacognitive awareness, and analytical reasoning—enables learners to internalize knowledge more effectively and apply it across contexts. The study underscores that the synergy between self-regulated learning and intelligence produces a holistic form of growth that integrates academic achievement with behavioural maturity.